Maximum Hosting Capacity Assessment of Distribution Systems with Multitype Distributed Energy Resources - Karna, Lokesh; Karki, Menaka (Journal of Science and Engineering, 2025)
Renewable energy resources are frequently integrated into the power systems to support load growth, reduce transmission and distribution losses, allow cost effective grid expansion, improve voltage profile and power quality. Hence, it is also necessary to determine the maximum capacity of distributed energy resources (DERs) that can be integrated into the distribution systems. In this study, the maximum capacity of distributed generations that can be integrated into the distribution systems has been assessed by a new DERs’ hosting capacity (DERHC) assessment method known as analytical optimal power flow method. The process is divided into two stages. In the first stage, the optimal location for the placement of single and multiple multitype renewable resources is found, and in the next stage, the maximum size of distributed generations is calculated, which satisfies operational constraints. This method for finding the maximum hosting capacity requires less computational time and is reliable for complex distribution networks. Moreover, battery storage devices have also been used to enhance the hosting capacity of the distribution systems. The simulations are performed using MATLAB coding and MATPOWER tool for the IEEE-33 bus radial distribution system and practical feeders of Nepal.